Effect of Peanut Consumption on Cardiovascular Risk Factors: A Randomized Clinical Trial and Meta-Analysis - Parilli-Moser, Isabella; Hurtado-Barroso, Sara; Guasch-Ferré, Marta; Lamuela-Raventós, Rosa M. (Frontiers in Nutrition, 2022)
Although numerous studies have reported the protective effect of nut consumption on cardiovascular risk, evidence for the role of peanuts in maintaining cardiometabolic health is inconclusive. Presented here are the results from the ARISTOTLE study, a parallel randomized controlled trial evaluating the impact of regular peanut intake on anthropometric, biochemical, and clinical measurements. The 63 healthy subjects that completed the study consumed their habitual diet plus either: a) 25 g/day of skin roasted peanuts (SRP, n= 21), b) two tablespoons (32 g)/day of peanut butter (PB, n= 23) or c) two tablespoons (32 g)/day of a control butter based on peanut oil (CB, n=19) for six months. In addition, a meta-analysis of clinical trials, including data from the ARISTOTLE study, was carried out to update the evidence for the effects of consuming peanuts, including high-oleic peanuts, and peanut butter on healthy subjects and those at high cardiometabolic risk. After a systematic search on PubMed, Web of Science, Cochrane Library and Scopus databases up to July 2021, 11 studies were found to meet the eligibility criteria. In the ARISTOTLE study, lower total cholesterol/HDL and LDL/HDL ratios were found in the SRP group compared to the CB group (p=0.019 and p=0.008). The meta-analysis of clinical trials revealed that peanut consumption is associated with a decrease in triglycerides (MD: -0.13; 95% CI, -0.20 to –0.07; p<0.0001) and that healthy consumers had lower total cholesterol and LDL/HDL ratios compared to the control groups (MD: -0.40; 95% CI, -0.71 to –0.09; p=0.01 and MD: -0.19; 95% CI, -0.36 to –0.01; p=0.03, respectively). However, individuals at high cardiometabolic risk experienced an increase in body weight after the peanut interventions (MD: 0.97; 95% CI, 0.54 to 1.41; p<0.0001), although not in body fat or body mass index. According to the dose-response analyses, body weight increased slightly with higher doses of peanuts. In conclusion, a regular consumption of peanuts seems to modulate lipid metabolism, reducing triglyceride blood levels.